Educational neuroscience - Patten, Kathryn E.; Campbell, Stephen R. (Malden, MA : Wiley, 2011)
Educational Neuroscience provides an overview of the wide range of recent initiatives in educational neuroscience, examining a variety of methodological concerns, issues, and directions. Encourages interdisciplinary perspectives in educational neuroscience. Contributions from leading researchers examine key issues relating to educational neuroscience and mind, brain, and education more generally. Promotes a theoretical and empirical base for the subject area. Explores a range of methods available to researchers. Identifies agencies, organizations, and associations facilitating development in the field. Reveals a variety of on-going efforts to establish theories, models, methods, ethics, and a common language.
Introduction: Educational Neuroscience / Kathryn E Patten, Stephen R Campbell -- Educational Neuroscience: Motivations, Methodology, and Implications / Stephen R Campbell -- Can Cognitive Neuroscience Ground a Science of Learning? / Anthony E Kelly -- A Multiperspective Approach to Neuroeducational Research / Paul A Howard-Jones -- What Can Neuroscience Bring to Education? / Michel Ferrari -- Connecting Education and Cognitive Neuroscience: Where will the Journey Take us? / Daniel Ansari, Donna Coch, Bert De Smedt -- Position Statement on Motivations, Methodologies, and Practical Implications of Educational Neuroscience Research: fMRI Studies of the Neural Correlates of Creative Intelligence / John Geake -- Brain-Science based Cohort Studies / Hideaki Koizumi -- Directions for Mind, Brain, and Education: Methods, Models, and Morality / Zachary Stein, Kurt W Fischer -- The Birth of a Field and the Rebirth of the Laboratory School / Marc Schwartz, Jeanne Gerlach -- Mathematics Education and Neurosciences: Towards Interdisciplinary Insights into the Development of Young Children's Mathematical Abilities / Fenna Van Nes -- Neuroscience and the Teaching of Mathematics / Kerry Lee, Swee Fong Ng -- The Somatic Appraisal Model of Affect: Paradigm for Educational Neuroscience and Neuropedagogy / Kathryn E Patten -- Implications of Affective and Social Neuroscience for Educational Theory / Mary Helen Immordino-Yang.
Includes bibliographical references and index.
Keywords: Educational psychology; Neurosciences; EDUCATION -- Educational Psychology; Educational psychology; Neurosciences; Electronic resource; Electronic books; Electronic books